2020
DOI: 10.1038/s41598-020-74268-6
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear association between blood lead and hyperhomocysteinemia among adults in the United States

Abstract: Evidence regarding the association between blood lead levels (BLL) and hyperhomocysteinemia (HHcy) in US adults was limited. We aimed to investigate the association of BLL with the risk of HHcy, and to examine possible effect modifiers using US National Health and Nutrition Examination Survey (NHANES) database. We performed a cross-sectional study using data from up to 9,331 participants aged ≥ 20 years of NHANES from 2001 to 2006. BLL was measured by atomic absorption spectrometry. HHcy was defined as plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
(55 reference statements)
4
7
0
Order By: Relevance
“…The prevalence of HHcy in China was updated to 37.2% in our study, as compared with the previous rate of 27.5% prior to 2012, as reported by Yang et al [13]. It remains high when compared with other developed countries, such as the United States (6.9%) [30] and Canada (19.1%) [31], but lower than Iran (73.1%) [32] and Africa (62.3%) [33]. Both subgroup analyses on the year of data collection and publication showed that the prevalence of HHcy varied substantially over time.…”
Section: Discussionsupporting
confidence: 58%
“…The prevalence of HHcy in China was updated to 37.2% in our study, as compared with the previous rate of 27.5% prior to 2012, as reported by Yang et al [13]. It remains high when compared with other developed countries, such as the United States (6.9%) [30] and Canada (19.1%) [31], but lower than Iran (73.1%) [32] and Africa (62.3%) [33]. Both subgroup analyses on the year of data collection and publication showed that the prevalence of HHcy varied substantially over time.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, folate insufficiency may impede arsenic (As) methylation and thereby aggravate arsenic toxicity [ 13 ]. Particularly, low levels of folate from dietary intake or in plasma can modify the associations between blood lead (Pb) and high hyperhomocysteinemia, an established risk factor for chronic vascular diseases [ 14 , 15 ]. However, correlations of the blood levels of metals and folate in plasma are not clearly known.…”
Section: Introductionmentioning
confidence: 99%
“…The reported prevalence of HHcy varied among populations residing in different regions. Based on a survey data from 2001 to 2006, Li et al found the prevalence of HHcy was 6.87% among 9331 US adult populations (aged ≥20 years) 23 . de Bree et al revealed in 2005 that the prevalence of HHcy was 10.9% among 25,489 European adult populations (aged ≥20 years) 24 .…”
Section: Discussionmentioning
confidence: 99%